VOCABULARY COMPLEXITIES FACED BY THE STUDENTS IN LEARNING ENGLISH OF EIGHTH GRADE AT SMP NEGERI 13 MAKASSAR - Rini Jumatri; Andi Tenri Ampa; Hilda Hafid (FKIP Unismuh Makassar, 2022)
This research aimed at finding out what the vocabulary complexities faced by students in learning English and its causes. This research applied the qualitative descriptive method that takes two months to collect data using interviews. This study involved 18 students from the eighth grade as participants.From the results of the interview test, most of the students' main complexities were meaning, pronunciation, spelling, grammar, vocabulary memorization, similarity of vocabulary, and foreign words. There are several factors that cause vocabulary complexity faced by students in learning English, namely lack of word understanding, written forms with different spoken forms, students do not master the alphabet, students are lazy to memorize vocabulary, students are confused with similar vocabulary, and students rarely read books.